Early anticoagulation in atrial fibrillation-related acute ischemic stroke: efficacy and safety profile - João Maria Guimarães e Matos Ribeiro Ferreira (2021)
Objectives: To understand the efficacy and safety profile of early anticoagulation in Atrial Fibrillation (AF)-related acute ischemic stroke (AIS) and to evaluate the main predictors of ischemic and hemorrhagic complications. Materials and Methods: We retrospectively evaluated patients hospitalized in a stroke unit due to AF-related AIS, between 2017-2019. Patients were divided according to anticoagulation initiation timing (0-4 days, 5-14 days, no anticoagulation at day 14). We assessed the following outcomes at 90 days: composite embolic recurrence (intracranial or systemic), composite hemorrhagic events, and favorable functional outcome (modified Rankin Scale (mRS) score 0-2 or equal to prestroke). Results: We included 395 patients. Median age was 80. Anticoagulation was initiated at days 0-4 in 134(33.9%) patients, at days 5-14 in 100(25.3%) and not initiated by day 14 in 161(40.8%). Factors associated with earlier anticoagulation included lower previous mRS, valvular AF and lower National Institutes of Health Stroke Scale (NIHSS) at Stroke Unit discharge. Ischemic recurrence occurred in 33(8.3%) patients, with higher odds in non-anticoagulated patients at day 14 compared to the remainder groups (OR:2.49,95%CI 1.07-5.80 vs. 0-4 days and 5.12,95%CI 1.49-17.58 vs. 5-14 days). In patients who started anticoagulation (n=288), composite hemorrhagic events occurred in 31(10.8%), with no significant differences between groups. Favorable outcome occurred in 157(40.2%) patients, with higher odds in those anticoagulated at 0-4 days versus 5-14 days, independently of age, previous mRS and discharge NIHSS. Conclusions: Early anticoagulation was significantly associated with lower embolic recurrence and better functional outcome at 90 days, with no significant increased hemorrhagic risk.